MEASURING CONNECTIVITY – A NEW APPROACH FOR THE GEOMETRIZATION OF THE LANDSCAPE AND FOR THE ENHANCEMENT OF COST-EFFECTIVENESS IN LANDUSE PLANNING - GÁBOR DEMETER (Acta Geographica Debrecina. Landscape & Environment Series)
The study aims to introduce a new method and approach for measuring the diversity of connectivity with the help of the landscape geometrization, in order to create a new variable useful in landscapemetrics and to decrease the costs of landscape planning if its main goal is the enhancement of connectivity. Using induction we identify the landscape elements with geometric elements, calculating the theoretical maximum line, section, intersection point (node) number and compare these values of the idealistic landscape to the values of the real landscape.